Foundational elements of communication in health and medicine: avenues for strengthening the marketing communications mix - James K. Elrod; John L. Fortenberry (BMC Health Services Research, 2020)
Abstract Background When one thinks of opportunities to engage patients, the marketing communications mix often is the first thing that comes to mind. Its five components of advertising, personal selling, sales promotion, public relations, and direct marketing represent tried and true pathways for establishing productive dialogues with customers of healthcare institutions. But in formulating and deploying the marketing communications mix, health and medical establishments must not neglect foundational elements which play vital communicative roles, impacting the perspectives of patients and influencing associated patronage. Discussion Many things communicate on behalf of healthcare organizations, including the people employed by them, the places in which they deliver services, and the brands that represent them. As foundational elements of communication, these must be addressed prior to formulating the marketing communications mix, as they influence and impact an institution’s entire communicative potential. Their initial development, however, is just the beginning, as these elements must be managed and maintained continually over the course of organizational life. This article profiles foundational elements of communication and discusses their importance in healthcare marketing, generally, and marketing communications, specifically, providing useful insights for maximizing communicative synergies. Conclusions Given the importance of engaging current and prospective patients, healthcare establishments must take steps to ensure exceptional prowess in this area, with communicative skills and abilities being of paramount importance. Proficient deployment of the marketing communications mix is essential, but healthcare providers must also be certain to direct attention toward foundational elements, ensuring that given institutions realize their full communicative potential.